Combating piracy, armed robbery against ships and maritime terrorism: a Malaysian perspective - Ahmed, Kyaw Hla Win @ Md Hassan; Mohamed Nafees, Seeni; Ali Mohamed, Ashgar Ali; Ansari, Abdul Haseeb (2015)
Historically, Malaysian waters have never been free from piracy and armed robbery against ships. Nevertheless, up to the present time, Malaysia is only a party to the United Nations Convention on the Law of the Sea 1982 (UNCLOS) and has not yet signed or rectified the Convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988 (SUA); the 2005 Protocol to the Convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988 (2005 Protocol); and, the Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia 2004 (ReCAAP). Besides, the Malaysian Penal Code does not deal with most of the maritime crimes envisaged under these international conventions as well as the regional agreement. Yet again, there is no specific local legislation to regulate piracy, armed robbery against ships and maritime terrorism in Malaysia. Accordingly, it is notable that Malaysian domestic legal frameworks are not comprehensive in suppressing such maritime crimes. Therefore, this paper primarily intents to analyse Malaysian criminal laws regulating some of the aforesaid maritime offenses and propose pragmatic recommendations for legal reforms in combating piracy, armed robbery against ships and maritime terrorism within and beyond Malaysian waters.